Growth, carcass characteristics and organ development of goat kids fed different levels of cow milk: Artificial milk feeding to kids - Khatun, Asma; Sarker, Md Bodruzzaman; Islam, Md Ahidul; Bari, Md Sadakatul; Amin, Md Ruhul; Moniruzzaman, Mohammad (Journal of the Bangladesh Agricultural University, 2019)
This study was conducted to determine the effect of feeding different levels of cow milk on growth, hematological parameters, carcass characteristics, rumen and testicular development of goat kids. Eighteen Black Bengal kids were randomly allocated to three groups on the basis of milk feeding levels, 10% (n=6), 15% (n=6), and 20% (n=6) of liveweight. The average liveweight of each group was 2.40 kg. The milk was fed at regular intervals daily up to 13 weeks of age when they were weaned. Blood samples were collected at 8 weeks of age to determine different blood components. At 16 weeks of age kids were sacrificed to examine carcass characteristics, rumen and testes development. Increasing levels of milk improved liveweight gain of kids. Kids fed 20% milk were heavier (7.78 ±0.37kg) at slaughter than others. Numbers of red blood cells were significantly higher in the 15% milk fed group than 20% milk fed group. Carcass weight and dressing percentage of meat did not differ significantly among the groups. Histological examination revealed that rumen papillae length (707.00 ± 37.07µm) and width (430.23 ± 29.86µm) were significantly higher in 20% milk fed kids than others. The sizes of right testicles were significantly wider in 20% milk fed kids than that of 10% groups of kids. In conclusion, cow milk could be fed to kids at the rate of 20% of their liveweight for maximum growth and organ development. <!--StartFragment --> J Bangladesh Agril Univ 17(4): 551–559, 2019